2018
DOI: 10.1111/jmwh.12734
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Postpartum Women after Mindfulness Childbirth Classes: A Qualitative Study

Abstract: Mindfulness skills helped class participants cope with physical and emotional challenges postpartum and fostered positive meaningful relationships with partners and newborns. Findings have implications for future research on mindfulness-based interventions and the postpartum experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…The main objective of the MBCP program [47] is to teach mindfulness meditation for decreasing stress during pregnancy, reducing pain and fear during childbirth, to support parenting with wisdom and compassion, and to interrupt intergenerational patterns of suffering [48]. The course schedule is 3 h once a week for nine weeks, a 7-h silent practice day on the weekend between classes 6 and 7, and a reunion class after all the women have given birth.…”
Section: Adapted Mbcp With Compassion Practices Tailored To the Spanimentioning
confidence: 99%
“…The main objective of the MBCP program [47] is to teach mindfulness meditation for decreasing stress during pregnancy, reducing pain and fear during childbirth, to support parenting with wisdom and compassion, and to interrupt intergenerational patterns of suffering [48]. The course schedule is 3 h once a week for nine weeks, a 7-h silent practice day on the weekend between classes 6 and 7, and a reunion class after all the women have given birth.…”
Section: Adapted Mbcp With Compassion Practices Tailored To the Spanimentioning
confidence: 99%
“…Mindfulness childbirth classes for pregnant women help them prepare for the labor and birth and increase the levels of maternal attachment and competence in motherhood [46]. The results from this study reveal that the MBCP curriculum helps women strengthen their inner processes of attention, awareness, nonreaction, and nonjudgment toward their children through their daily parenting interactions.…”
Section: Discussionmentioning
confidence: 77%
“…Moreover, the differences were more signi cant 42 days after delivery than at three days, indicating that the mindfulness intervention's effects continued for at least 42 days postpartum. Finally, Kantrowitz-Gordon et al [47] conducted a qualitative study with a convenience sample and found that mindfulness exercises helped new mothers switch roles and nd joy in early parenting. The participants also discovered the bene ts of living in the present, which can improve family relationships, help them empathize with their partners, and be more likely to experience happiness, which, in turn, can increase life satisfaction and happiness; this is consistent with our research.…”
Section: Discussionmentioning
confidence: 99%